LEGAL-HISTORICAL CIRCUMNSTANCES OF THE LEGAL (POLITICAL) ACTIVISM IN THE FIGHT AGAINST TERRORISM IN CONTEMPORARY LEGAL HISTORY OF THE REPUBLIC OF CROATIA - Dagen, Tomislav (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Considering the contemporary legal (normative) forms of combating terrorism in the European Union, it is unquestionable that behind every action (including a political one) there is a legal basis/foundation on which such action is based. Certain historical events from the end of the 20th century and the beginning of the 21st century, both in the world and in the European Union, as well as in the Republic of Croatia, prompted causality between the historical events/political decisions and legal standardisation/legal activism in the fight against terrorism. Normative regulation of the fight against terrorism will in(directly) reflect on the political action and normative regulation of the fight against terrorism even after the EU accession, due to the commonly known “war against terrorism”, the “Arab Spring”, and the occurrence of terrorist attacks in Europe, as well as the process of the EU accession and the EU membership. Normative regulation of the fight against terrorism, will have a multi-faceted role, considering the example of the Republic of Croatia from the legal-historical perspective. Firstly, it implies belonging to the global/European group of countries which normatively regulate the fight against terrorism; secondly, it implies harmonising Croatian legal standards which regulate the issue of combating terrorism with acquis communautaire of the European Union during the Croatia’s EU accession process; and thirdly, legal standardisation of the fight against terrorism is causally linked to national security, as well as to the security of the European Union and the neighbouring countries of the Republic of Croatia.